2015
DOI: 10.1007/s13353-015-0301-x
|View full text |Cite
|
Sign up to set email alerts
|

Random regression models to account for the effect of genotype by environment interaction due to heat stress on the milk yield of Holstein cows under tropical conditions

Abstract: The present study had the following objectives: to compare random regression models (RRM) considering the time-dependent (days in milk, DIM) and/or temperature × humidity-dependent (THI) covariate for genetic evaluation; to identify the effect of genotype by environment interaction (G×E) due to heat stress on milk yield; and to quantify the loss of milk yield due to heat stress across lactation of cows under tropical conditions. A total of 937,771 test-day records from 3603 first lactations of Brazilian Holste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
4
28
0
4
Order By: Relevance
“…Consequently, selection for higher MY, F% or P% may result in a poor response of the poorly adapted animals to heat stress. A genetic antagonism between general production level and specific ability to respond to heat stress has also been reported in other studies on dairy cattle (Aguilar et al, 2009;Carabaño et al, 2014;Santana et al, 2016). The genetic trends show that, for MY, there was considerable genetic progress in the general production level over the years studied in all three lactations.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Consequently, selection for higher MY, F% or P% may result in a poor response of the poorly adapted animals to heat stress. A genetic antagonism between general production level and specific ability to respond to heat stress has also been reported in other studies on dairy cattle (Aguilar et al, 2009;Carabaño et al, 2014;Santana et al, 2016). The genetic trends show that, for MY, there was considerable genetic progress in the general production level over the years studied in all three lactations.…”
Section: Discussionsupporting
confidence: 78%
“…This could have been due to the fact that part of the farms included in the present study had no effective cooling system. In a study involving a large single Brazilian Holstein herd, Santana et al (2016) identified a THI value of 66 as the heat stress threshold for MY in primiparous cows. However, the herd studied used cooling systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during recovery phase, milk decline was recorded to be much lesser of about 1.2±0.32 kg [69]. In an experiment on Holstein cows to assess the decrease in milk yields due to heat stress in tropical conditions, a yield loss of 0.23 kg day -1 was observed for unit rise of THI above 66 [70]. In southern Brazil, [71] observed 21% milk yield loss in commercial heard of Holstein cows due to heat stress.…”
Section: Assessment Of Heat Stress Using Heat Index Chartsmentioning
confidence: 99%
“…The resulting model is a multiple-trait, multiple-environment model with a variety of interactions, in which computational issues may arise due to the increase in the number of parameters being estimated. It has been shown that RRMs can account simultaneously for the additive genetic effect and some degree of GxE in longitudinal traits in animal breeding by allowing for the estimation of genetic (co)variance components and breeding values over the whole trajectory of a time-dependent trait and environmentdependent covariate (Brügemann et al, 2011;Santana et al, 2016;Bohlouli et al, 2019). In plant breeding, therefore, this model may provide considerable biological insights into the mechanisms determining performance in specific environments, making it a worthwhile method for study in future research.…”
Section: Non-additive Effects and Gxementioning
confidence: 99%